2016
DOI: 10.1021/acssynbio.6b00048
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen Ways to Reroute Cooperative Communication in the Lactose Repressor: Engineering Regulatory Proteins with Alternate Repressive Functions

Abstract: The lactose repressor (LacI) is a classic genetic switch that has been used as a fundamental component in a host of synthetic genetic networks. To expand the function of LacI for use in the development of novel networks and other biotechnological applications, we engineered alternate communication in the LacI scaffold via laboratory evolution. Here we produced 14 new regulatory elements based on the LacI topology that are responsive to isopropyl β-d-1-thiogalactopyranoside (IPTG) with variation in repression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 28 publications
1
64
1
Order By: Relevance
“…Engineering Non-natural Operator DNA Binding with Alternate Allosteric Phenotypes (I A ADR ). Alternate phenotypes for cooperative communication in the LacI scaffold have been previously engineered by Wilson et al 3,13 by first introducing I s point mutations that block allosteric communication, followed by EP-PCR to generate mutations capable of conferring alternate repressive function. EP-PCR was applied to the allosteric core of LacI (residues 62−322), therefore leaving the DNA binding domain (DBD) of LacI unaffected, which led us to hypothesize that the DBD could be altered while leaving allosteric function unaffected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Engineering Non-natural Operator DNA Binding with Alternate Allosteric Phenotypes (I A ADR ). Alternate phenotypes for cooperative communication in the LacI scaffold have been previously engineered by Wilson et al 3,13 by first introducing I s point mutations that block allosteric communication, followed by EP-PCR to generate mutations capable of conferring alternate repressive function. EP-PCR was applied to the allosteric core of LacI (residues 62−322), therefore leaving the DNA binding domain (DBD) of LacI unaffected, which led us to hypothesize that the DBD could be altered while leaving allosteric function unaffected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The genes for all LacI variants were based on pLacI (Novagen), which features a low copy number p15A origin, a chloramphenicol resistance marker, and the gene for the lactose repressor regulated with a constitutive LacI promoter. Mutations to the DNA binding domain were introduced via routine site directed mutagenesis using Phusion DNA Polymerase, summarized in Meyer et al 3 A reporter plasmid system was constructed starting with the pZS*22-sfGFP reported in Richards et al 13 This plasmid features a low copy number pSC101* origin of replication, and a Kanamycin resistance marker. The region of the plasmid excluding the promoter and operator was PCR amplified, visualized on an Agarose Gel, and Gel Extracted (Omega).…”
Section: Construction Of Laci Mutants and Operator Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, PurR and TrpR act as repressors when in their ligand bound form 37, 38 , LacI and TetR as repressors only in their apo-form 39, 40 , while BenM acts as a co-activator when bound to CCM 41 . Indeed, previous directed evolution studies have demonstrated the identification of aTFs with reversed mode-of-action 2325, 30 . To probe the evolvability of BenM towards an inversion-of-function (i.e., deactivator/CCM as a co-repressor) using toggled selection following one round of directed evolution, we first sorted the aTF variant library for highly fluorescent variants in the absence of any ligand, indicative of auto-induction (OFF)(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, starting from allosterically-dead aTF variants with constitutive DNA-binding, semi-structure-guided mutagenesis has been used to identify and evolve new biosensors with changes in both dynamic output range and inversion of function (ie. inverse-repression) 2325 . In most of these library studies, the mutagenized aTF libraries were characterized based on ligand-induced expression of fluorescent reporter genes or antibiotic resistance genes for multiplexed selection of aTF variants responding to the ‘trait’ of interest using biosensor readouts based on fluorescence-activated cell sorting (FACS) or cell survival, respectively.…”
Section: Introductionmentioning
confidence: 99%